MAKING PROPERTY OUTLAWS: Law and Relegation. (27th September 2021) - Blomley, Nicholas; ,
Abstract: Drawing from community‐based research in the Downtown Eastside, the poorest part of Vancouver, Canada, a neighbourhood long demonized as an 'outlaw zone', we suggest that what may appear to be illegal property practices in the area's infamous Single Room Occupancy (SRO) hotels are, in fact, harder to detach from formal legality than supposed. We characterize the state's withdrawal of tenancy law from SRO in the 1970s as productive of property outlaws. A form of legal relegation, outlawry places SRO residents in a space of lesser protection, stripping them of rights. A space of decades of systematic legal relegation, the outlaw zone is a product of law, not its antithesis, predicated on organized forms of devaluation and discrimination.